Etyma-Based Lexical Variation in Body-Parts and Kinship Vocabulary of Lampung Cikoneng Dialect - Sri Munawarah; Linda Sari Wulandari (Linguistik Indonesia, 2026)
The etyma group was used to study lexical variation in the Lampung Cikoneng language. This study focused on the distribution of etyma based on 52 body part vocabulary words and 25 kinship vocabulary words. Data collection techniques used purposive sampling, namely 15 informants from 15 observation points. This study used interview techniques. The results of the study show that there is high lexical variation in the Lampung Cikoneng language. Lexical variation in body part vocabulary shows a varied distribution of etyma of 1-7, with the group of 2 etyma being the most numerous. Meanwhile, kinship vocabulary shows a variation of one to five etyma, with three etyma as the most dominant pattern. The variations found include lexical and phonological differences and reflect the intensive influence of contact between the Lampung language and the Javanese and Sundanese languages. These findings confirm the existence of strong internal differentiation and enrich the study of dialectology and the dynamics of change in the Lampung language in the context of a multilingual society.